Kedudukan Ahli Waris Yang Berkelamin Ganda (Khuntsa)Menurut Hukum Waris Islam - Elisabeth Pudyastiwi; Doni Adi Supriyo; Eti Mul Erowati (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
The occurrence of someone who has dual genitalia in general in society has various impacts. Many cases have emerged that require handling. The purpose of this study is to determine the legal status of the heirs of Indonesian citizens who have dual genitalia (khuntsa) and how the rights to inherit the inheritance of heirs who have dual genitalia (khuntsa) or whose status is in doubt according to Islamic law. This type of research uses normative legal research which is based on the formulation of the problem and the purpose of the research. With the method of legislative approach and conceptual approach. The results of the study explain that the inheritance rights of khuntsa have not been explicitly regulated in the KHI, and in the Qur'an there has been no inheritance law for khuntsa. In determining the legal status of this khuntsa, it can be seen from the signs of maturity and where it urinates as mentioned in the hadith narrated by HR. Ibn 'Abbas, and can perform sex change operations. The heirs agree in calculating the level of the khuntsa musykil part by estimating and calculating it as a man then as a woman. Khuntsa and other heirs receive the smallest estimated share, while the rest that is still in doubt is withheld until the legal status of the khuntsa is clear. Keywords: Heirs, khuntsa, Islamic law